Penguatan Literasi dan Kesadaran Partisipasi Politik Mahasiswa Perempuan sebagai Warganegara Demokratis - Robyan Endruw Bafadal; Siti Hidayatul Jumaah; M. Dirangse Samudra; Baiq Dewi Kamariani (Lembaga Pengembangan Kinerja Dosen, 2026)
Low levels of political literacy and political participation awareness among female university students remain a challenge for strengthening democracy at the local level. This condition is also found among female students in East Lombok, who tend to perceive political participation narrowly and lack the skills and confidence to engage actively as citizens. This community service program aims to enhance political literacy, participatory awareness, and the capacity of female students to understand and practice political participation in a critical and responsible manner. The program was implemented at the Institut Teknologi Sosial dan Kesehatan Muhammadiyah Selong using a community organizing approach integrated into the academic learning process. The methods included participatory discussions, mentoring, simulations, and critical reflection, positioning female students as active subjects throughout the activities. The results indicate an improvement in participants’ understanding of the meaning and forms of political participation, increased confidence in expressing opinions, and the emergence of new awareness regarding their roles as democratic citizens. In addition, a female student discussion group was formed as a space for collective learning and an early platform for local leadership. This program highlights the role of higher education institutions in promoting social transformation and strengthening women’s political participation at the local level.